Tinjauan Maqashid Syariah terhadap Hierarki Hukum Hewan Kurban Terindikasi Penyakit Mulut dan Kuku dalam Fatwa Majelis Ulama Indonesia - Muhtarul Alif (Mutawasith: Jurnal Hukum Islam, 2022)
This study aims to examine the hierarchy of sacrificial animals in the MUI fatwa number 32 of 2022 from the maqashid sharia perspective. MUI's role as an aspirator of community religious expression to the government makes MUI have a central role in community religious practices, MUI fatwa number 32 of 2022 regarding guidelines for sacrificial worship during an outbreak of Mouth and Nail Disease is an example. The fatwa classifies sacrificial animals into four categories. The categorization of the results of ijtihad from the MUI makes maqashid sharia the foundation for providing solutions to the maintenance of religion, soul, mind, honor and economic aspects. The method used in this study is a qualitative method with an analytical descriptive approach. The results of the study show that the hierarchy of sacrificial animals according to the MUI's ijtihad considers aspects of maintaining religion by continuing to strive for sacrificial worship, aspects of protecting the soul by paying attention to public health, aspects of preserving the mind by closing the possibility of damage to brain nerve cells, aspects of maintaining honor by closing opportunities for accusations of Islamic unscientificity , and aspects of maintaining the economy by allowing sacrifices with certain conditions.